Highly thermally resistant, hydrophobic poly(vinyl alcohol)-silica hybrid nanofibers - (:unkn) unknown (SERBIAN CHEMICAL SOC, 2018)
In this paper, the preparation of hydrophobic and crosslinked poly(vinyl alcohol)/silica organic-inorganic hybrid nanofibers via the sol-gel electrospinning method is reported. Silica was produced through the acetic acid catalyzed reaction of a silica precursor consisting of dimethyldimethoxysilane (DMDMOS), methyltrimethoxysilane (MTMS), tridecafluoro-1,1,2,2-tetrahydrooctyltriethoxysilane (FAS1313; Dynasylan (R) F 8261) and phenyltrimethoxysilane (PTMS; Dynasylan (R) 9165) in a 2-propanol-water mixture. Hybrid nanofibers were obtained by electrospinning the silica precursor and an aqueous PVA solution. Chemical, structural, thermal and surface analyses were conducted by Fourier-transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy/energy-dispersive X-ray (SEM/EDX) and water contact angle (WCA) methods, respectively. The obtained hybrid nanofibers were insoluble in aqueous solution. SEM images displayed that highly crosslinked and porous structures were obtained and the average fiber diameters of poly(vinyl alcohol) (PVA)/silica nanocomposites were around 70 nm. A nanofiber surface with a water contact angle of 130 degrees was achieved.
Keywords: poly(vinyl alcohol); electrospinning; sol-gel; hybrid nanofibers; MEMBRANES; COATINGS; NANOCOMPOSITES; COMPOSITE